Association between socio-demographic factors and reasons for medical care in Mexican adults - Mónica Alethia Cureño-Díaz; José Ángel Hernández-Mariano; Erika Gómez Zamora; Viridiana Judith González Zavala (Journal of Family Medicine and Primary Care)
Background: The occurrence and distribution of diseases result from the interaction between biological, environmental, economic, and social factors. Although Mexico has made significant progress in the health sector, there are several problems associated with the social determinants of health, which are linked to social factors such as gender, age, income, and schooling, among others. Therefore, the purpose of this study was to evaluate the relationship between socio-demographic factors with the main reasons for medical care among patients seen at a public healthcare institution in Mexico City. Materials and Methods: A cross-sectional analytical study in which the clinical records of 1,018 adult patients who attended any of the services provided by a public healthcare institution in Mexico City between August and December 2023 were examined. Results: The odds of seeking medical care for neoplastic diseases were lower in men, among patients with their own home, with balanced economic status and surplus, but higher in people aged 40 years and older, in those with fewer intra-household and public services in their homes. Conclusions: Strategies for prevention, management, and control of chronic and infectious diseases need to consider social inequalities, addressing the determinants of health to generate a significant impact on the health of the population.